2018
DOI: 10.1002/ar.24024
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: PIM3 Functions as Oncogenic Factor and Promotes the Tumor Growth and Metastasis in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the common human malignancies. Discovery and identification of novel therapeutic target is imperative to improve the prognosis of CRC patients. As a member of the PIM family, PIM3 has been found to be overexpressed in a variety of cancerous tumors. In this study, we evaluated the expression of PIM3 in CRC tissues and analyzed the role of PIM3 in CRC. Our results showed that PIM3 expression was significantly higher in CRC tissues compared with adjacent noncancerous tissues. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Besides, through bioinformatics analysis, we also discovered that there were the binding sites between microRNA-203b (miR-203b) and Recombinant Pim-3 Oncogene (PIM3), suggesting that miR-203b may target PIM3. Several studies have also uncovered that PIM3 acts as a carcinogen in various cancer processes (27)(28)(29). Therefore, we speculated that miR-203b/PIM3 axis plays a crucial role in the progression of GC.…”
Section: Original Articlementioning
confidence: 90%
“…Besides, through bioinformatics analysis, we also discovered that there were the binding sites between microRNA-203b (miR-203b) and Recombinant Pim-3 Oncogene (PIM3), suggesting that miR-203b may target PIM3. Several studies have also uncovered that PIM3 acts as a carcinogen in various cancer processes (27)(28)(29). Therefore, we speculated that miR-203b/PIM3 axis plays a crucial role in the progression of GC.…”
Section: Original Articlementioning
confidence: 90%
“…Previously, it was reported that PIM3 aggravates cell proliferation and invasion in liver cancer through Rho GTPase pathway (Dang et al, 2020). Further, PIM3 was confirmed to serve as an oncogene and promote metastasis of colorectal cancer cells (Qi et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…Previously, it was reported that PIM3 aggravates cell proliferation and invasion in liver cancer through Rho GTPase pathway (Dang et al., 2020). Further, PIM3 was confirmed to serve as an oncogene and promote metastasis of colorectal cancer cells (Qi et al., 2019). More importantly, the present study verified that LINC01232 promotes the malignancy of BC cells via targeting miR‐370‐5p/PIM3 axis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Cai QQ et al demonstrated that sulfatide interaction with the BRD1 mediates acetylation and is important for the regulation of integrin αV gene expression in hepatocarcinoma ( 27) and similarly could have the same effect in AT/RT. While proviral integration of Moloney murine 3 (PIM3) is associated with Distal Muscular Dystrophy, it has also been demonstrated to function as an oncogenic factor promoting tumor growth in colorectal cancer (28) and hepatoblastoma (29). The modulator of VRAC current 1 (MLC1) is associated with Megalencephalic Leukoencephalopathy with subcortical cysts and it could be related to melanoma survival and chemoresistance through mitogen-activated protein kinases (MAPK) -extracellular signal-regulated kinases (ERK) pathway (30,31).…”
Section: Discussionmentioning
confidence: 99%